Tilapia Culture in South Latitudes: First Report of Successful Fattening in Hot Springs of Buenos Aires Province, Argentina - Damian Luis Castellini; Aldo Nahuel Zanazzi; Angelina Gorosito; Enzo Damián Tranier; María Fernández-Subiela; Juan Carlos Mallo (Department of Aquaculture, 2020)
In the present work, the feasibility of fattening Oreochromis niloticus specimens on a pilot scale in a geothermal water resource located in the Southeast of the province of Buenos Aires was analyzed. Before placing the culture units, physical and chemical characteristics of hot spring were studied to evaluate its suitability for tilapia farming. In the experimental stage, two hundred specimens with an average weight of 14.5 ± 1.8g were placed in two floating cages (1.30x1x1m) (100 individuals per cage) and they were harvested at 140 days. The specimens were fed 3 times a day with a commercial pelleted feed with a content of 35% of proteins. Monthly samplings were carried out to evaluate growth (weight and total length), survival, and water samples were collected to measure their physical-chemical characteristics. The results of the water analysis showed a high quality in the hot springs (Simplified Water Quality Index=88). The fattening results showed an average final weight of 423-435.9 g, a survival of 87-91%, a SGR 1.47- 1.49% / day and the FCR was estimated at 1.05-1.07 for each cage respectively. We can conclude that this hot spring has the necessary water conditions to obtain excellent weight gains during the fattening period for the O. niloticus specimens. The present study represents the first Nile tilapia culture in the southernmost thermal waters, setting a precedent for future ventures in the area.